122k views
3 votes
PLEASE HELP HURRY!!!!!!!

15 POINTS FOR CORRECT ANSWER!!!!!

Given that x = 4 + 5i and y = 2 - 9i, match the equivalent expressions.

PLEASE HELP HURRY!!!!!!! 15 POINTS FOR CORRECT ANSWER!!!!! Given that x = 4 + 5i and-example-1
User Jing
by
5.5k points

2 Answers

2 votes

x•y = 53-26i 2x•y = 106-52i

-x+3y= 2-32i

4x-y = 14+39i

User Mjepson
by
4.5k points
3 votes

As it has been given that
x=4+5i,
y=2-9i.

We need to find the value of the following:

(i)
4x-y, substituting the value of 'x' and 'y' in the expression, we get:


4(4+5i)-(2-9i)=4* 4+4* 5i-2+9i=16+20i-2+9i


=14+29i

So,
4x-y=14+29i

(ii)
-x+3y, substituting the value of 'x' and 'y' in the expression, we get:


-(4+5i)+3(2-9i)=-4-5i+3* 2-3 * 9i=-4-5i+6-27i


=2-32i

So,
-x+3y=2-32i

(iii)
x * y, we need to substitute the value of 'x' and 'y' in the expression, for this, we can use distributive property of multiplication that says,


a(b+c)=a * b+ a * c

Using the distributive property of multiplication:


(4+5i)*(2-9i)=4 * 2-4 * 9i+5i * 2-5i * 9i


=8-36i+10i-45i^2

Now, we know that
i * i=i^2=-1

We get,
8-36i+10i-45 * (-1)=8-26i+45


=8+45-26i=53-26i

Therefore,
x * y=
53-26i.

(iv) We have,
2x * y, we need to substitute the value of 'x' and 'y' in the expression, we get:


2(4+5i)* (2-9i)

Again, we can use distributive property of multiplication that says,


a(b+c)=a * b+ a * c

So,


2(4+5i) * (2-9i)=2* 4+2 * 5i*(2-9i)


=8+10i *(2-9i)=8* 2-8 * 9i+10i * 2-10i * 9i


=16-72i+20i-90i^2

since,
i^2=-1

we get,


16-72i+20i-90 * (-1)=16-52i+90


=106-52i

Therefore,


2x * y=106-52i


User Yeah
by
5.7k points